The Pol Pot Regime race, power and genocide in Cambodia under the Khmer Rough,1975-79 - Kiernan, Ben (Yale University Press, 1999)
The Khmer Rouge revolution turned Cambodia into grisly killing fields, as the Pol Pot regime murdered or starved to death a million and a half of Cambodia's eight million inhabitants. This book - the first comprehensive study of the Pol Pot regime - describes the violent origins, social context, and course of the revolution, providing a new answer to the question of why a group of Cambodian intellectuals imposed genocide on their own country.